Review Paper of Current Status and Strategies with regards to Dark Sky Tourism in the Northern Periphery and Arctic Regions - Uí Dholáín, Martina; Silvennoinen, Daisy (Karelia University of Applied Sciences, 2023)
This NPA GLOW2.0 Northern Periphery and Arctic project survey aimed at identifying the preservation efforts and initiatives for Dark Sky areas and light pollution in participating NPA regions. For the study, the existing strategies to Dark Sky Tourism in Ireland, Finland, Northwest Iceland, and Norway within the context of the NPA region have been examined. With a focus on regional development and policy implementation, the study investigates the unique approaches and initiatives adopted by these countries, shedding light on the workings of their respective regional landscapes.